4 - Challenges of the Devolved Health Sector in Kenya: Teething Problems or Systemic Contradictions? - Kimathi, Leah (Africa Development, 2017)
The promulgation of the new constitution in Kenya in August 2010 effectively ushered in devolution as the latest and highest form of decentralization in Kenya. The health sector was the largest service sector to be devolved under this new governance arrangement. The rationale for devolving the sector was to allow the county governments to design innovative models and interventions that suited the unique health needs in their contexts, encourage effective citizen participation and make autonomous and quick decisions on resource mobilization and management possible issues. However, the sector in nearly all counties is currently bedevilled with monumental challenges ranging from capacity gaps, human resource deficiency, lack of critical legal and institutional infrastructure, rampant corruption and a conflictual relationship with the national government. The net effect of these challenges is the stagnation of healthcare and even a reversal of some gains according to health indicators. No doubt what is needed to guarantee an all-inclusive rights- based approach to health service delivery is its proper institutionalization to ensure good governance and effective community participation. This must however be accompanied by wider governance reforms as envisaged in the new constitution for the sustainability of Healthcare Reforms.